The Regulated Cell Death and Potential Interventions in Preterm Infants after Intracerebral Hemorrhage - Wu, Yanan; Sun, Yanyan; Wang, Xiaoyang; Zhu, Changlian (Current Neuropharmacology, 2023)
Intracerebral hemorrhage (ICH) in preterm infants is one of the major co-morbidities of preterm birth and is associated with long-term neurodevelopmental deficits. There are currently no widely accepted treatments to prevent ICH or therapies for the neurological sequelae. With studies broadening the scope of cell death, the newly defined concept of regulated cell death has enriched our understanding of the underlying mechanisms of secondary brain injury after ICH and has suggested potential interventions in preterm infants. In this review, we will summarize the current evidence for regulated cell death pathways in preterm infants after ICH, including apoptosis, necroptosis, pyroptosis, ferroptosis, autophagy, and PANoptosis as well as several potential intervention strategies that may protect the immature brain from secondary injury after ICH through regulating regulated cell death.
Keywords: Intracerebral hemorrhage